If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + 5i) + -1(5 + -3i) = 0 Remove parenthesis around (3 + 5i) 3 + 5i + -1(5 + -3i) = 0 3 + 5i + (5 * -1 + -3i * -1) = 0 3 + 5i + (-5 + 3i) = 0 Reorder the terms: 3 + -5 + 5i + 3i = 0 Combine like terms: 3 + -5 = -2 -2 + 5i + 3i = 0 Combine like terms: 5i + 3i = 8i -2 + 8i = 0 Solving -2 + 8i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8i = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 8i = 0 + 2 8i = 0 + 2 Combine like terms: 0 + 2 = 2 8i = 2 Divide each side by '8'. i = 0.25 Simplifying i = 0.25
| 9p-4q+11p+7q= | | a+a-3b+2b= | | c+d+2c-2d= | | 4(t-4)+3t=32-t | | y=100-(t^2-6t) | | (2x-3)(2x-3)=(x-3)(4x+11) | | -3(-13x-37)=-9(-46+4x) | | 3x+x+16=50 | | 4y=-5x+-20 | | (7t+5)-(3t-5)= | | 3x+3y+4=x+2y+1 | | 4x-8=-2x-5 | | (x-6)(x+6)=(x-6)(x-6) | | (x-6)(x+6)=(x-6)x(x-6) | | y-5.9=7.22 | | 8x+18=30 | | 2x^4y^2z^2= | | 0=9x+0.25y | | 3Xsquare-13X-10=0 | | 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z |